Aesthetic measures for assessing graphic screens - Chek, David Ling Ngo; Azman Samsudin,; Rosni Abdullah, (INST INFORMATION SCIENCE, ACADEMIA SINICA, TAIPEI 115, TAIWAN, 2000)
An important aspect of screen design is aesthetic evaluation of screen layouts. However, no one knows how to measure aesthetic value. This article proposes a theoretical approach to capturing the essence of the artists' insight. We introduce several aesthetic measures for graphic screens. The results of our informal study demonstrate close relationships between artistic vision and the proposed measures.